Radiogenic Pb in xenotime trapped in nanoscale inclusions of apatite during fluid alteration - Joseph, Cilva; Fougerouse, Denis; Reddy, Steven; Olierook, Hugo; Tacchetto, Tomaso; Kennedy, Allen; Saxey, David; Rickard, William; Denyszin, Steven; Dodd, Aaron (Elsevier, 2023)
This study focuses on the low-temperature mineralogical response of xenotime, a phosphate mineral routinely used as a geochronometer, to fluid-assisted alteration. The studied xenotime grain (z6413) comes from a ∼ 1000 Ma pegmatite from the Grenville Province, Canada, and is commonly used as reference material for U–Pb analyses. At the microscale, the grain has a mottled texture, sub-micrometer porosity, and small domains dark in backscattered electron (BSE) images that are characterised by curviplanar, sharp boundaries. The small dark BSE domains are associated with Th-U-rich inclusions and larger porosity (2–3 μm) and are interpreted to result from localised fluid-assisted coupled dissolution-reprecipitation. Sensitive high-resolution ion microprobe (SHRIMP) U–Pb analyses of unaltered and fluid-affected domains yield concordant crystallisation dates, irrespective of the textural domains. The apparently unaltered xenotime domain was characterised at the nanoscale to determine if the grain was affected by fluids beyond the altered domains defined by BSE imaging. Transmission electron microscopy (TEM) imaging results indicate the presence of randomly distributed Ca + Pb nanoscale precipitates. Atom probe tomography (APT) reveals the presence of spherical clusters (4 to 18 nm in size) enriched in radiogenic Pb, Ca, and Si atoms, which, combined with TEM observations, are interpreted as nanoscale inclusions of apatite. In addition to the inclusions, a dislocation enriched in Ca and fluid mobile elements such as Cl, Li, Na, and Mn was imaged from APT data indicating percolating of fluids further than the reaction front. APT 206Pb/238U nanogeochronology indicates that the nanoscale inclusions of apatite formed at 863 ± 28 Ma, 100–150 Ma after crystallisation of the host xenotime, with its formation attributed to fluid metasomatism. This study shows that fluid-xenotime reaction caused Pb* to be redistributed at the nanoscale, recording the timing of metasomatism. However, at the scale of SHRIMP analytical spot (10 μm), xenotime is concordant, indicating that Pb was not mobile at the microscale and fluid-altered xenotime can preserve its crystallisation age. Although the studied grain shows a limited amount of altered domains in BSE imaging, nanoscale analyses reveal a more pervasive re-equilibration of the minerals through the percolation of fluids along dislocations.